Perspectives on contraceptive implant use in women living with HIV in Cape Town, South Africa: a qualitative study among primary healthcare providers and stakeholders - Brown, Anna (BMC Public Health, 2019)
BACKGROUND: This study explored primary healthcare provider and HIV/contraception expert stakeholder perspectives on South Africa’s public sector provision of contraceptive implants to women living with HIV. We investigated the contraceptive service-impact of official advice against provision of implants to women using the HIV antiretroviral drug, efavirenz, issued by the South African National Department of Health (NDoH) in 2014. METHODS: Qualitative data was collected in Cape Town in 2017 from primary healthcare contraceptive providers in four clinics that provide implants, as well as from other expert stakeholders selected for expertise in HIV and/or contraception. In-depth interviews and a group discussion explored South Africa’s implant introduction and implant provision to women living with HIV. Data was analysed using an inductive thematic analysis approach. RESULTS: Interviews were conducted with 10 providers and 10 stakeholders. None of the four clinics where the providers worked currently offered the implant to women living with HIV. Stakeholders confirmed that this was consistent with patterns of implant provision at primary healthcare facilities across Cape Town. Factors contributing to providers’ decisions to suspend provision of the implant to women living with HIV included: inadequate initial and ongoing provider training; interpretation of NDoH communications about implant use with efavirenz; provider unwillingness to risk harming clients and concerns about professional liability; and other pressures related to provider capacity. CONCLUSIONS: All South African women, including those living with HIV, should have access to the full range of contraceptive options for which they are medically eligible. Changing guidance should be initiated and communicated in consultation with primary-level providers and service beneficiaries. Guidance issued to providers needs to be clear and fully evidence-informed, and its correct interpretation and implementation facilitated and monitored. Guidance should be accompanied by provider training, as well as counselling messages and tools to support providers. Generalized retraining of providers in rights-based, client-centred family planning, and in particular implant provision for women with HIV, is needed. These recommendations accord with the right of women living with HIV to access the highest possible standard of sexual and reproductive healthcare, including informed contraceptive choice and access to the contraceptive implant.